Byproducts as a sustainable source of cosmetic ingredients - Machado, Manuela (2024)
The cosmetic industry has been driven to implement sustainable practices that can help it overcome its high carbon footprint and intensive raw material extraction needs. The adoption of circular economy and bioeconomy concepts within the industry has been regarded as a solution for this problem, and within these concepts, byproducts’ incorporation in the cosmetics production chain, either as bioactive or as a structural component, is only a logical step. With this in mind, this review aims to provide an overarching view of the application of byproducts in cosmetics with emphasis not only on their potential biological properties but also on all the regulations and societal and economic impacts associated with byproducts’ incorporation into cosmetics and how they can help this industry.